Histone H3K9 demethylase JMJD1A modulates hepatic stellate cells activation and liver fibrosis by epigenetically regulating peroxisome proliferator‐activated receptor γ. Issue 5 (21st January 2015) - Jiang, Yan; Wang, Sheng; Zhao, Yuanyuan; Lin, Chengzhao; Zhong, Fan; Jin, Li; He, Fuchu; Wang, Haijian
ABSTRACT: As a central event in liver fibrogenesis, hepatic stellate cell (HSC) transdifferentiation involves loss of regulation by adipogenic transcription factors such as peroxisome proliferator‐activated receptor γ; (PPARγ), which is epigenetically silenced during HSC activation. We hypothesized that JMJD1A, an H3K9 demethylase involved in adipogenic metabolism, could regulate PPARγ. In human HSC cell line, rat primary HSCs, and carbontetrachloride‐induced mouse liver fibrogenesis model, we down‐regulated the expression of JMJD1A using small interfering or short hairpin RNAs, and overexpressed its wild‐type and mutant. We analyzed the effects of JMJD1A manipulation on the histone di‐methyl‐H3K9 (H3k9me2) status of PPARγ gene and the expression of PPARγ and fibrosis markers using chromatin immunoprecipitation, real‐time quantitative RT‐PCR and Western blot, and also investigated the in vitro and in vivo consequences on liver fibrosis and necrosis by Masson or hematoxylin‐eosin staining, respectively. JMJD1A knockdown in HSCs correlated with reinforced H3K9me2 in the PPARγ gene promoter, and its down‐regulation in both mRNA and protein led to increased expression of fibrosis markers, which could be consistently rescued by JMJD1A overexpression. Jmjd1a knockdown in situ resulted in significantly increased expression of α‐smooth muscle actin ( P = 0.005) and Col1a ( P = 0.036), strengthened production of collagens ( P = 0.028), and remarkably enhanced necrosis ( P = 0.007) 4 weeks after treatment. This study suggests JMJD1A as a novel epigenetic regulator that modulates HSC activation and liver fibrosis through targeting PPARγ gene expression.—Jiang, Y., Wang, S., Zhao, Y., Lin, C., Zhong, F., Jin, L., He, F., Wang, H. Histone H3K9 demethylase JMJD1A modulates hepatic stellate cells activation and liver fibrosis by epigenetically regulating peroxisome proliferator‐activated receptor γ. FASEB J. 29, 1830‐1841 (2015). www.fasebj.org